The pathological role of B cells in systemic lupus erythematosus: From basic research to clinical - Yu Feng; Ming Yang; Haijing Wu; Qianjin Lu (Taylor & Francis Group, 2020)
Systemic lupus erythematosus (SLE) is an autoimmune disease that often occurs in females of child-bearing age. It involves multiple systems and severely threatens human life. One of the typical characteristics of SLE is the formation of immune complexes with autoantibodies produced by B cells that target various autoantigens, thus indicating the pivotal role of B cells in the pathogenesis of SLE. Increasing evidence has shown abnormal expression of B cells in the peripheral blood of SLE patients. Moreover, numerous studies have shown that B cells in SLE patients are abnormally activated, as well as aberrantly differentiated, and are involved in the inflammatory cytokine milieu, abnormal transcription factor activity, and signalling pathways. Several biological therapies targeting B cells, such as anti-CD20 antibodies, have been intensively studied in preclinical and clinical trials. However, the results have not met expectations. Therefore, new therapies targeting B cells are in great need. This review will summarize the latest progress in basic research on B cells to better understand the pathogenesis of SLE and will discuss the outcomes of B-cell-targeting treatments that provide potential therapeutic targets and strategies for SLE. Studies have clarified high levels of IL-21 in serum from SLE patients and animal models. IL-21 promotes B cell differentiation, which results in antibodies accumulation leads to SLE. Therefore, further studies on IL-21 will give new perspectives on SLE treatments. In addition, the application of drugs targeting plasma cell depletion in SLE patients may also achieve satisfied results in treatment.